Treatment of venous thromboembolism with vitamin K antagonists: patients’ health state valuations and treatment preferences - Locadia, Mirjam; Bossuyt, Patrick M.M.; Stalmeier, Peep F.M.; Sprangers, Mirjam A.G.; van Dongen, Carlo J.J.; Middeldorp, Saskia; Bank, Ivan; van der Meer, Jan; Hamulyák, Karly; Prins, Martin H. (Thrombosis and Haemostasis, 2004)
Determining the optimal duration of vitamin K antagonist (VKA) therapy for patients with venous thromboembolism (VTE) requires a weighting of the benefits and risks of treatment. The objectives of our study were to investigate patient variability in health state valuations associated with VKA therapy and treatment preferences, and to investigate the extent to which valuations and treatment preferences are associated with prior experience with these health states and other patient characteristics. Valuations of outcomes after VTE scaled from 0 (tantamount to death) to 1 (tantamount to perfect health) were elicited from 53 patients who had experienced VTE, 23 patients who had experienced major bleeding during treatment, and 48 patients with the post-thrombotic syndrome. In addition, patients’ treatment preferences were evaluated using treatment trade-off questions. Median health state valuations ranged from 0.33 for ‘non-fatal haemorrhagic stroke’ to 0.96 for ‘no VKA treatment’. Variability between patients was substantial. Patients’ treatment preferences also varied: 25% of patients chose cessation of treatment, regardless of the probability of recurrent VTE presented, whereas 23% of patients were never willing to choose cessation of treatment. Differences in valuations and treatment preferences were not associated with type of event experienced. Due to the substantial and unpredictable variability in valuations and treatment preferences, recommendations regarding treatment duration should be tailored to patients’ specific values and concerns.
Keywords: Venous thromboembolism; health state valuations; treatment preferences